2010
DOI: 10.1007/s12272-010-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of new 4,6-disubstituted pyrimidine, pyrazoline, and pyran derivatives

Abstract: A number of new 2,6-didisubstituted pyrimidine, pyrazoline, and pyran derivatives were synthesized starting from their chalcone derivative. The synthesized compounds displayed different degrees of antimicrobial activity against Bscillus subtilis (Gram-positive), Pseudomonas aeruginosa (Gram-negative), and Streptomyces species (Actinomycetes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Both the previously supposed techniques provided products in good to excellent yields with simple and mild reaction conditions. The authors are afraid to forget that true intermediate 2t could be isolated in good yield with the thermal reaction condition (see more in the supplementary file). On the other hand, in the case of using ethylcyanoacetate and ethylacetoacetate with chalcone in the presence of ammonium acetate via four‐component reaction afforded two products of pyrano[2,3‐b]pyridine derivatives 2d and 2e as outlined in (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the previously supposed techniques provided products in good to excellent yields with simple and mild reaction conditions. The authors are afraid to forget that true intermediate 2t could be isolated in good yield with the thermal reaction condition (see more in the supplementary file). On the other hand, in the case of using ethylcyanoacetate and ethylacetoacetate with chalcone in the presence of ammonium acetate via four‐component reaction afforded two products of pyrano[2,3‐b]pyridine derivatives 2d and 2e as outlined in (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Electron‐withdrawing substituents lower the HOMO energy, such as halogens, due to the inductive effect of halogen that results in the decrease in electron density from the σ space of benzene ring, particularly 3,4‐dichloro derivatives, thereby decreasing the energy of HOMO . Designing chalcone derivatives with a high degree of bonding linearity (κ2 index) with groups that increase molecular weight [high value of absorption, distribution, metabolism, and excretion (ADME) weight] represents a positive contribution to the antibacterial activity . P‐glycoprotein is an ATP‐dependent multidrug resistance efflux transporter that plays an important role in anticancer drug resistance and in the pharmacokinetics of medicines .…”
Section: Resultsmentioning
confidence: 99%
“…Several derivatives of the pyran or fused pyran ring systems are endowed with di erent types of biological activities [1,2]. It has been reported that pyran derivatives exhibit antimicrobial activity, growth stimulating e ects, antifungal and plant growth regulation e ects, antitumor activity, central nervous system (CNS) activity and hypotensive e ect [3].…”
Section: Discussionmentioning
confidence: 99%
“…Dihydropyran derivatives represent one of the most active classes of compounds possessing a wide spectrum of biological activities [1][2][3], including anticoagulant, insecticidal, anthelminthic, hypnotic, antifungal, phytoalexin, and HIV protease inhibition. The interesting biological activity of these dihydropyrans made these compounds attractive targets in organic synthesis [4].…”
Section: Discussionmentioning
confidence: 99%